The in situ light microenvironment of corals - Wangpraseurt, Daniel (2014)
We used a novel diver-operated microsensor system to collect in situ spectrally resolved light fields on corals with a micrometer spatial resolution. The light microenvironment differed between polyp and coenosarc tissues with scalar irradiance (400–700 nm) over polyp tissue, attenuating between 5.1- and 7.8-fold from top to base of small hemispherical coral colonies, whereas attenuation was at most 1.5-fold for coenosarc tissue. Fluctuations in ambient solar irradiance induced changes in light and oxygen microenvironments, which were more pronounced and faster in coenosarc compared with polyp tissue. Backscattered light from the surrounding benthos contributed > 20% of total scalar irradiance at the coral tissue surface and enhanced symbiont photosynthesis and the local O2 concentration, indicating an important role of benthos optics for coral ecophysiology. Light fields on corals are species and tissue specific and exhibit pronounced variation on scales from micrometers to decimeters. Consequently, the distribution, genetic diversity, and physiology of coral symbionts must be coupled with the measurements of their actual light microenvironment to achieve a more comprehensive understanding of coral ecophysiology.